2018
DOI: 10.1155/2018/8932817
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic, Electrophysiological, and Biochemical Profiles in Children with Attention Deficit Hyperactivity Disorder and/or Epilepsy

Abstract: Attention deficit hyperactivity disorder (ADHD) is among the most prevalent neurobehavioral disorders affecting children worldwide. The prevalence of ADHD is higher in children with epilepsy. Despite the plethora of conducted work, the precise cause of ADHD is not identified yet. We studied here the sociodemographic, clinical, electrophysiological, and biochemical profiles of children with ADHD, epilepsy, and ADHD with epilepsy. Subjects were divided into 4 groups (25 child/group): I—control, II—ADHD, III—epil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…In accordance with previous studies, we observed sex differences in our results regarding inattention, hyperactivity/impulsivity and ADHD symptoms. Differences have been reported previously [61][62][63], with the diagnosis of ADHD being more common in male children and adolescents, with a male-to-female ratio ranging from 2:1 to 10:1 [64]. In line with this, in the present study, boys had more symptoms than girls.…”
Section: Sex Differencessupporting
confidence: 88%
“…In accordance with previous studies, we observed sex differences in our results regarding inattention, hyperactivity/impulsivity and ADHD symptoms. Differences have been reported previously [61][62][63], with the diagnosis of ADHD being more common in male children and adolescents, with a male-to-female ratio ranging from 2:1 to 10:1 [64]. In line with this, in the present study, boys had more symptoms than girls.…”
Section: Sex Differencessupporting
confidence: 88%
“…Similarly, Abd El Naby et al verified that there was a strong significant correlation between PedsQL scores with IQs (p value = 0.001) [17]. Other studies have confirmed that ADHD with epilepsy is inversely correlated with the QOL and that treating ADHD significantly improves the QOL of CWE [73,74].…”
Section: Discussionmentioning
confidence: 88%
“…Attention-deficit/hyperactivity disorder (ADHD) is one of the most widespread disorders in CWE [15,16]. ADHD is generally characterized by persistent inattention, hyperactivity, and impulsivity [17]. Furthermore, several studies found that ADHD children may have electroencephalogram (EEG) abnormalities such as interictal epileptiform discharges (IEDs) or localization of IEDs foci [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…4 of these studies found that there were no significant differences between sex and ADHD symptoms [ 33 , 39 , 42 , 47 ]. 5 studies found that males had more ADHD symptoms than females [ 11 , 28 , 34 , 41 , 50 ]. One study [ 26 ] compared iron status (iron sufficient, ID without anemia, ID anemia) and sex, and found a statistically significant difference (p<0.001) between the aforementioned groups.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from 4 ADHD studies which measured only SF as a primary iron marker [ 41 43 , 46 ] and 1 ADHD study which measured only SF and SI [ 50 ], all studies measured both iron-related and RBC-related markers for ID. A significant association of SF, but not of RBC-related or other iron markers was found in 9 ADHD [ 14 , 28 32 , 35 , 37 , 39 ] and 2 ASD studies [ 17 , 54 ].…”
Section: Resultsmentioning
confidence: 99%